Chuva de sementes e sistemas sexuais de espécies lenhosas em um trecho de floresta ombrófila densa, Espírito Santo - Perini, Monique (2016)
The plant reproductive biology has been studied in order to understand aspects of speciation and structure of plant communities, and as a consequence to obtain information that support biodiversity conservation actions. The goal of this study was to characterize the seed rain and the frequency of sexual systems woody species in a stretch of montane tropical rainforest at the Caparaó National Park, Espírito Santo. The study area was divided in seven plots distributed along the Santa Marta valley , in the city of Ibitirama, ES. The seed rain was sampled from November/ 2012 to October/ 2013. Seed rain composition was estimated by absolute and relative density and species richness, and are graded according to their ecological characteristics as sexual system, pollination and dispersal syndromes and fruit type. To measure the correlation between sexual systems with ecological characteristics a correspondence analysis (CA) was conducted. The correlation between variables such as temperature, rainfall, face exposure and deposition of leaf litter with the seed rain parameters of richness and density was calculated using the Spearman test. Comparisons between the richness and density of seeds per plot and the months were tested by Kruskal-Wallis test (p <0.05) and Friedman (p <0.05). These analyses showed that the seed rain tends to follow a seasonal pattern with deposition peaks in periods of greater precipitation and reduction of species richness when the altitude. Sexual systems of woody species recorded in the seed rain, showed the pattern suggest for tropical rainforests, with 73% of hermaphrodite species, 14% dioecius and 12% monoecious.